Novel epoxy activated hydrogels for solving lactose intolerance - Elnashar, Magdy; Hassan, M. (Hindawi Publishing Corporation, 2014)
"Lactose intolerance" is a medical problem for almost 70% of the world population. Milk and dairy products contain 5-10% w/v lactose. Hydrolysis of lactose by immobilized lactase is an industrial solution. In this work, we succeeded to increase the lactase loading capacity to more than 3-fold to 36.3 U/g gel using epoxy activated hydrogels compared to 11 U/g gel using aldehyde activated carrageenan. The hydrogel's mode of interaction was proven by FTIR, DSC, and TGA. The high activity of the epoxy group was regarded to its ability to attach to the enzyme's -SH, -NH, and -OH groups, whereas the aldehyde group could only bind to the enzyme's -NH2 group. The optimum conditions for immobilization such as epoxy chain length and enzyme concentration have been studied. Furthermore, the optimum enzyme conditions were also deliberated and showed better stability for the immobilized enzyme and the Michaelis constants, Km and Vmax, were doubled. Results revealed also that both free and immobilized enzymes reached their maximum rate of lactose conversion after 2 h, albeit, the aldehyde activated hydrogel could only reach 63% of the free enzyme. In brief, the epoxy activated hydrogels are more efficient in immobilizing more enzymes than the aldehyde activated hydrogel.